1985
DOI: 10.21273/jashs.110.6.769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoot, Root, and Shank Chilling during Rest in Apple and Peach on Growth Resumption and Carbohydrates

Abstract: One-year-old nursery trees of ‘Redchief’ apple (Malus × domestica Borkh.) on MM106, M9, and seedling rootstocks and ‘Redhaven’ peach [Prunus persica (L.) Batsch.] on Lovell rootstock were subjected to root and shoot chilling treatments for 1500 and 1200 hr, respectively, followed by forcing in the greenhouse. Budbreak and new shoot and root growth were increased by chilling the apple root and shoot. In contrast, only shoot chilling increased these parameters in peach. When shanks of clonal apple rootstocks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…1 and Table 1). finding agrees with results reported previously for 1-year-old 'Delicious' trees maintained under greenhouse conditions (16). However, by the end of the first growing season, there was very little difference in number of extension shoots between treatments (Table 2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1 and Table 1). finding agrees with results reported previously for 1-year-old 'Delicious' trees maintained under greenhouse conditions (16). However, by the end of the first growing season, there was very little difference in number of extension shoots between treatments (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Several studies have indicated that this chilling requirement resides primarily within the buds (8,11). However, recent investigations have shown that chilling the root system during dormancy is also necessary for maximum vegetative budbreak and new root growth (14,16). Trees with root systems maintained at nonchilling temperatures (15° to 17°C) had significantly less budbreak and new shoot growth than those with roots at 5° (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Budbreak and root development were both significantly greater after chilling (Fig. 1), in agreement with previous observations and experimental results (Young and Werner, 1985). Budbreak was greatest in M.7a and least in M.26 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Soluble carbohydrates in the xylem appear to be used rapidly when trees are placed in greenhouse conditions. The subsequent increase presumably reflects breakdown of starch reserves in the roots and lower trunk that occurs before and during budbreak (Young and Werner, 1985;Young et al, 1987). Sauter and Ambrosius (1986) found that soluble sugars, mainly sucrose, glucose, and fructose, decreased markedly in Populus xylem sap during the first 5 days at 21C after chilling, then began to increase after 1 0 days.…”
Section: Discussionmentioning
confidence: 99%